2009
DOI: 10.1073/pnas.0907236107
|View full text |Cite
|
Sign up to set email alerts
|

A role for suppressed incisor cuspal morphogenesis in the evolution of mammalian heterodont dentition

Abstract: Changes in tooth shape have played a major role in vertebrate evolution with modification of dentition allowing an organism to adapt to new feeding strategies. The current view is that molar teeth evolved from simple conical teeth, similar to canines, by progressive addition of extra "cones" to form progressively complex multicuspid crowns. Mammalian incisors, however, are neither conical nor multicuspid, and their evolution is unclear. We show that hypomorphic mutation of a cell surface receptor, Lrp4, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
1
42
0
2
Order By: Relevance
“…The enamel prisms provide greater mechanical strength and increase in mechanic imbrication are more adapted to act as masticatory dental elements, which features a small enamel prismless layer temporary on the tooth surface, or even mice, which have a thin layer of enamel surface (Bishop 1995, Koussoulakou 2009, Ohazama et al 2010). The underlying dentin enamel tubules showed a pattern in which the tubules are interleaved by a more compacted dentin, called intertubular dentin, and this pattern is found in other mammals, even in humans (Forssell-Ahlberg et al Muylle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The enamel prisms provide greater mechanical strength and increase in mechanic imbrication are more adapted to act as masticatory dental elements, which features a small enamel prismless layer temporary on the tooth surface, or even mice, which have a thin layer of enamel surface (Bishop 1995, Koussoulakou 2009, Ohazama et al 2010). The underlying dentin enamel tubules showed a pattern in which the tubules are interleaved by a more compacted dentin, called intertubular dentin, and this pattern is found in other mammals, even in humans (Forssell-Ahlberg et al Muylle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of how morphologically-distinct tooth classes and complex tooth crown shapes develop in mammals is largely derived from research on mice (Munne et al, 2010; Ohazama et al, 2010a; Ohazama et al, 2010b). The first morphological sign of tooth development begins with a thickening of oral epithelium along the maxillary and mandibular arches early in the embryonic period before individual teeth can be distinguished (Leche, 1892; Leche, 1895; Orban, 1980; Ruch et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of one of these mutants (Sostdc1) showed that the supernumerary incisor developed on the lingual side of the normal one, and this tooth was considered to belong to a different tooth generation, corresponding to the revival of either the replacement incisor (Munne et al, 2009) or of a rudimentary lacteal incisor (Murashima-Suginami et al, 2007). The supernumerary incisor of Lrp4-null mice has been considered as having the same origin as the supernumerary incisor of Sostdc1 mutants (Ohazama et al, 2010). In the sprouty mutants reported here, the concomitant developmental origin and the side-by-side organization of the two incisors indicate that they must be considered as the same tooth generation.…”
Section: The Duplicated Incisors Belong To the Same Generation And Armentioning
confidence: 99%